Determination of digital technologies preferences of educational researchers. Issue 1 (28th December 2020) - Fırat, Mehmet; Altınpulluk, Hakan; Kılınç, Hakan
Abstract : Purpose: This study aims to investigate the preferences of 96 educational researchers on the use of digital technologies in scientific research. Design/methodology/approach: The study was designed as a quantitative-dominant sequential explanatory mixed-method research. Findings: Despite the spreading use of advanced technologies of big data and data mining, the most preferred digital technologies were found to be data analysis programs, databases and questionnaires. The primary reasons of using digital technology in scientific research were to collect data easily and quickly, to reduce research costs and to reach a higher number of participants. Originality/value: The use of digital technologies in scientific research is considered a revolutionary action, which creates innovative opportunities. Through digitalized life, probably for the first time in history, the educational researchers have analytical information, which we can benefit from more than the individual's own statements in research involving human factor. However, there are a few studies that investigated the preferences of educational researchers who use digital technologies in their scientific research.